Is reverse frontal cranioplasty eligible for the correction of both the forehead deformities and the intracranial hypertension in craniosynostosis? Comparison of the preoperative and postoperative intracranial volumes. Issue 9 (September 2021) - Kulker, D.; Louisy, A.; Listrat, A.; Travers, N.; Pare, A.; Laure, B.
Abstract: Background: This study aimed to describe the surgical technique of reverse frontal cranioplasty (RFC), the aesthetical modification as well as the modification of intracranial volume (ICV) to assess its potential eligibility for the treatment of the intracranial hypertension (IH). Materials and methods: A retrospective monocentric study included the patients with a history of craniosynostosis with a forehead deformity who underwent RFC. A subjective outcome questionnaire (SOQ) was conducted with each patient or their parent to determine their level of satisfaction after RFC. Pre- and postoperative computed tomography (CT) scans were analyzed and compared to investigate the ICV change and fronto-nasal angle. Results: Eleven patients were included in the study (6 female and 5 male) with a mean age of 10.9 years old (range 3–23 years) and an average follow-up of 4.5 years (1–11 years). All patients responded to the questionnaire with a high level of overall satisfaction (mean 9.1/10). The mean preoperative FNA was 134° ± 5° while the mean postoperative angle was 126.4° ± 6, corresponding to an average decrease of 7.6° (95% CI, 4.0–11.2°; p < 0.001). One patient with preoperative IH had a clinical recurrence during the follow-up. The ICV was significantly higher after the surgery (p < 0.0001), with an average increase of 3.2% (95% CI, 2.3–4.1%). Conclusion: Reverse (RFC) is a useful technique for the correction of the frontal malformations related to craniosynostosis, such as a sloping forehead and/or a lack of the supraorbital projection. Regarding the limited gain of intracranial volume (ICV), it should not be used alone as primary cranial expansion surgery for craniosynostosis with intracranial hypertension (IH).